A preliminary validation study of PuO2 incorporation into zirconolite glass-ceramics. (30th January 2018) - Thornber, Stephanie M.; Stennett, Martin C.; Vance, Eric R.; Chavara, Dorji T.; Watson, Ian; Jovanovic, Miodrag; Davis, Joel; Gregg, Daniel; Hyatt, Neil C.
Abstract: Zirconolite glass-ceramics are being developed as potential wasteforms for the disposition of Pu wastes in the UK. Previous studies utilised a variety of surrogates whilst this work uses both cold-press and sinter and hot isostatic press methods to validate the wasteform with PuO2 . A cold press and sinter sample was fabricated as part of a validation study for plutonium incorporation in hot isostatically pressed (HIPed) wasteforms. The results confirmed the cold-press and sinter, achieved successful waste incorporation and a microstructure and phase assemblage that was in agreement with those expected of a HIPed equivalent. A HIP sample was fabricated of the same composition and characterised by SEM and XRD. Results were in agreement with the sintered sample and achieved complete waste incorporation into the glass-ceramic wasteform. These samples have demonstrated successful incorporation of PuO2 into glass-ceramic HIPed wasteforms proposed for processing Pu-based waste-streams in the UK.